An animal research and a chemical composition analysis of a Chinese prescription for pulmonary fibrosis: Yangfei Huoxue Decoction. (5th December 2019) - Liu, Xiao; Chen, Hui; Su, Guangbao; Song, Ping; Jiang, Miao; Gong, Jiening
Abstract: Ethnopharmacological evidence: Pulmonary fibrosis (PF) is a progressive disease characterized by the aberrant accumulation of fibrotic tissue in the lungs parenchyma, associated with significant morbidity. Few effective drugs have been developed to reverse PF or even halt the disease progression. Yangfei Huoxue Decoction (YHD), a Traditional Chinese Medicine, which consisted of Astragalus membranacus(AM), Glehnia littoralis(GL), Schisandra chinensis(SC), Salvia miltiorrhiza Bunge(SB), Reynoutria japonica(RJ), Ligusticum chuanxiong(LX), and Euonymus alatus(EA), has been used in China for the treatment of PF for many years with remarkable efficacy. According to the clinic observation of the results, we conducted experiments on animals, the process of BLM-induced pulmonary fibrosis in rats was interfered by YHD, through the detection of pulmonary fibrosis rats' blood cells and plasma, we selected the related molecules that may exert proinflammatory(IL-1β), promote angiogenesis(vascular endothelial growth factor, VEGF). For further explicitly research, we should know what the chemical composition the prescription (YHD) contains and what the related bioactive components have. In accordance with in-house library and evaluating the characteristic MS fragmentation patterns, the schisandra chinensis methanol, lignin, flavonol, polyphenol, tanshinone, salvianolic acid, anthraquinone, ligustrazine, etc. had a retardant and inhibitory effect on the development and formation of pulmonary fibrosis. These results will aid in the quality control of YHD, as well as provide fundamental data for further pharmaco-mechanisms studies. Aim of the study: To discover the pulmonary immune related bioactive components of YHD. Materials and methods: Animal Experiment :144 SD rats, based on the principles of randomization divided into eight groups, Control group, bleomycin(BLM) group, BLM + dexamethasone(BLM + DXM) group, BLM + Yangfei(YF) group, BLM + Huoxue(HX) group, BLM + high-doseYHD(YHD-H) group, BLM + medium-doseYHD(YHD-M) group, and BLM + low-doseYHD(YHD-L) group, each group of 18 rats. After endotracheal administration of Bleomycin by tracheotomy, rats were sacrificed on day 7, day 14 and day 28, blood and plasma were taken at the same time. Respectively, the VEGF, an immune molecule associated with angiogenesis, and IL-1β in plasma were detected by ELISA at three time periods. Component testing: 100 g YHD were constituted of SB 15 g, LX 12 g, EA 10 g, RJ 15 g, AM 20 g, GL 20 g and SC 8 g. All herbs were obtained from Beijing Tong Ren Tang (Group) Co ltd. The voucher specimens were identified by Prof. Jiening Gong (Nanjing University of Chinese Medicine). YHD were extracted by sonication with 1 L ethanol/water (70:30, v/v) for two cycle (1 h per cycle) at room temperature. The combined extracts were filtered, condensed, and reconstituted with 50 mL methanol before analysis. Standard Cianidanol, Ferulic Acid, Polydatin, Calycosin 7-O-glucoside, Tanshinone IIA, Salvianolic acid B, Schizandrol A, and Isoimperatorin were prepared in methanol. After centrifuging at 20, 000 rpm for 10 min, 4 μL supernatant was injected into the Ultra-Performance Liquid Chromatography coupled with Quadrupole Time-of-Flight tandem mass spectrometry (UPLC/QTOF-MS E ) combined with UNIFI informatics platform for analysis. Conclusion: The experiment results revealed that the vascularized VEGF, inflammatory factor expression of IL-1β was restrained by YHD. The UPLC/QTOF-MS E method, an automatic database screening platform and the characteristic MS fragmentation patterns have efficiently facilitated the post data process, so we test for the identification of major components in YHD by this technology, more than seven or more active ingredients, the results showed that YHD contained a total of 55 components, including 11 lignans, 12 flavonoids, 7 tanshinones, 9 organic acid, 5 polyphenols, 4 anthraquinones, 5 senkyunolides and 2 others. Based on this, we can ensure the discovery and analysis of biologically active compounds in YHD, as well as provide a reference for the quality evaluation. We expect the method presented here could be applied to other multi-component TCM formula. In addition, we can conduct more in-depth research, such as mechanism research, molecular detection, gene target and so on. Graphical abstract: Image 1